1997
DOI: 10.1182/blood.v90.1.323.323_323_330
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Epstein-Barr Virus (EBV) Latent Membrane Protein-1 Gene and Promoter Region: Identification of Four Variants Among Wild-Type EBV Isolates

Abstract: Sequence variations in the Epstein-Barr virus (EBV) encoded latent membrane protein-1 (LMP-1) gene have been described in a Chinese nasopharyngeal carcinoma-derived isolate (CAO), and in viral isolates from various EBV-associated tumors. It has been suggested that these genetic changes, which include loss of a Xho I restriction site (position 169425) and a C-terminal 30-base pair (bp) deletion (position 168287-168256), define EBV genotypes associated with increased tumorigenicity or with disease among particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
4
53
0
1
Order By: Relevance
“…[44][45][46][47] Several different sequence variations have been detected in the oncogenic viral latent membrane protein 1 (LMP1) of EBV in NPC tumors 44,[48][49][50] ; however, there remains no strong evidence to suggest an increased risk associated with different EBV variants. 33,[49][50][51][52] In the current study, we found that differentiated nonkeratinizing NPC incidence was increasing among all sex and race groups, leading to speculation of an increased role of EBV in NPC in the United States. Exploratory analyses into SEER incidence trends of extranodal NK/T-cell lymphoma, a form of non-Hodgkin's lymphoma consistently associated with EBV, 53-67 demonstrated significant increases in this cancer type among both sexes over this time period, further supporting the possibility of an increasing role in EBV etiology in US malignancies (see Supporting Fig.…”
Section: Discussionmentioning
confidence: 65%
“…[44][45][46][47] Several different sequence variations have been detected in the oncogenic viral latent membrane protein 1 (LMP1) of EBV in NPC tumors 44,[48][49][50] ; however, there remains no strong evidence to suggest an increased risk associated with different EBV variants. 33,[49][50][51][52] In the current study, we found that differentiated nonkeratinizing NPC incidence was increasing among all sex and race groups, leading to speculation of an increased role of EBV in NPC in the United States. Exploratory analyses into SEER incidence trends of extranodal NK/T-cell lymphoma, a form of non-Hodgkin's lymphoma consistently associated with EBV, 53-67 demonstrated significant increases in this cancer type among both sexes over this time period, further supporting the possibility of an increasing role in EBV etiology in US malignancies (see Supporting Fig.…”
Section: Discussionmentioning
confidence: 65%
“…The majority of reports regarding the 30 bp-deletion of LMP1 have shown that this variation is widely spread worldwide [Hu et al, 1991;Sandvej et al, 1997;Correa et al, 2004;See et al, 2008;Tiwawech et al, 2008;Bobek et al, 2010;da Costa et al, 2015] -Table II. A recent meta-analysis, evaluated the association of this variation with NPC development and showed an association of del-LMP1 variant with NPC development described that the association is only observed in Asiatic populations while no association is observed for European and North African countries [da Costa et al, 2015].…”
Section: Variations In Ebv Genomementioning
confidence: 99%
“…To establish whether delayed activation of STAT is also observed with variants of LMP1 other than the B95.8 form, BL41 clones expressing NGFR-LMP1 containing the Cterminus of LMP1 isolated from PTLD-derived SLCL were studied. The clones were named according to the LMP1 group nomenclature (18) but group C clones were derived from two different cell lines, MF4 and VB5, obtained from two different PTLD patients and are indicated as C(M) and C(V), respectively. STAT1 is only activated after 24 h of NGFR-LMP1 cross-linking, while no significant increase in p-Tyr STAT3 was detected at either 30 min or 24 h ( Figure 3B and C).…”
Section: Activation Of Stat1 By Lmp1 Is Delayed Bl41 Cells Expressingmentioning
confidence: 99%